2013
DOI: 10.1007/s00422-013-0567-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of suppression of sustained neuronal spiking under high-frequency stimulation

Abstract: Using Hodgkin–Huxley and isolated subthalamic nucleus (STN) model neurons as examples, we show that electrical high-frequency stimulation (HFS) suppresses sustained neuronal spiking. The mechanism of suppression is explained on the basis of averaged equations derived from the original neuron equations in the limit of high frequencies. We show that for frequencies considerably greater than the reciprocal of the neuron’s characteristic time scale, the result of action of HFS is defined by the ratio between the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
(116 reference statements)
3
32
1
Order By: Relevance
“…7. gumo and Morris-Lecar neurons as well as the fourdimensional Hodgkin-Huxley model. The generic nature of this effect is further substantiated by our previous findings in isolated subthalamic nucleus model neurons [27]. This phenomenon is common not only for neuronal systems, but it is typical for any self-sustained oscillator.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…7. gumo and Morris-Lecar neurons as well as the fourdimensional Hodgkin-Huxley model. The generic nature of this effect is further substantiated by our previous findings in isolated subthalamic nucleus model neurons [27]. This phenomenon is common not only for neuronal systems, but it is typical for any self-sustained oscillator.…”
Section: Discussionsupporting
confidence: 74%
“…Based on the results obtained in our simple model presented here and in our previous study [27] we may expect high-frequency stimulation to effectively suppress low-frequency oscillations, such as theta and beta band LFP oscillations, and to induce high-frequency oscillations (in the range of the stimulation frequency) of the membrane potential. The functional role of these high-frequency, stimulus-induced oscillations in a neuronal network still remains to be investigated.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Unfortunately, the DBS treatment is often accompanied with undesirable side effects. In recent papers [41][42][43], it has been demonstrated that the high frequency forcing eventually stabilizes the UFP of the neuronal oscillators in case of HH, FHN, and other neuronal models. Two shortcomings of the DBS have been emphasized [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the recent papers [14,15] detailed investigations, both analytical and numerical, have been carried out towards understanding of the mechanism of the existing DBS therapy technique. We hope that search for alternative methods, in particular using experimental approach, can contribute to the problem of the treatment of the Parkinson disease.…”
Section: Discussionmentioning
confidence: 99%